Development of Tutorial-Based Teaching Books in Basic Embroidery Engineering Courses - Rambe, Armaini; Juliarti; Dewi, Eka Rahma; Annida, Ulfa (Edukasi, 2024)
The lack of availability of teaching materials on basic embroidery techniques means students learn embroidery by relying on examples from previous assignments and searching for assignments on YouTube. Even though this example does not contain detailed steps, students still experience difficulties in understanding embroidery techniques, the art of arranging thread, adjusting and placing the right colors for good, embroidered decoration. Therefore, there is a need for tutorial-based textbooks on learning basic embroidery techniques. The aim of the research is to produce a tutorial-based textbook on basic embroidery techniques courses in the fashion design education study program at Medan State University. The development model uses the ADDIE model. The data collection technique uses a questionnaire and is analyzed using qualitative descriptive analysis. Validation of teaching materials is carried out by material experts and media experts. The validity test of material experts obtained 83.9% and media experts obtained 81.73% in the good category. The results of small group trials obtained 81.8%, medium scale trials obtained 82.87% and large group trials obtained 85.3%. The results of the research show that tutorial-based teaching materials are suitable for use in learning basic embroidery techniques courses. It is hoped that this tutorial-based teaching material can help teachers convey practical material in detail and make it easier for students to understand basic embroidery techniques independently.